Phosphate loading does not improve 30-km cycling time-trial performance in trained cyclists - Pope, H.; Davis, M.; Delgado-Charro, M. B.; Peacock, O. J.; Gonzalez, J.; Betts, J. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2023)
Phosphate is integral to numerous metabolic processes, several of which strongly predict exercise performance (i.e., cardiac function, oxygen transport, and oxidative metabolism). Evidence regarding phosphate loading is limited and equivocal, at least partly because studies have examined sodium phosphate supplements of varied molar mass (e.g., mono/di/tribasic, dodecahydrate), thus delivering highly variable absolute quantities of phosphate. Within a randomized cross-over design and in a single-blind manner, 16 well-trained cyclists (age 38 ± 16 years, mass 74.3 ± 10.8 kg, training 340 ± 171 min/week; mean ± SD) ingested either 3.5 g/day of dibasic sodium phosphate (Na2HPO4: 24.7 mmol/day phosphate; 49.4 mmol/day sodium) or a sodium chloride placebo (NaCl: 49.4 mmol/day sodium and chloride) for 4 days prior to each of two 30-km time trials, separated by a washout interval of 14 days. There was no evidence of any ergogenic benefit associated with phosphate loading. Time to complete the 30-km time trial did not differ following ingestion of sodium phosphate and sodium chloride (3,059 ± 531 s vs. 2,995 ± 467 s). Accordingly, neither absolute mean power output (221 ± 48 W vs. 226 ± 48 W) nor relative mean power output (3.02 ± 0.78 W/kg vs. 3.08 ± 0.71 W/kg) differed meaningfully between the respective intervention and placebo conditions. Measures of cardiovascular strain and ratings of perceived exertion were very closely matched between treatments (i.e., average heart rate 161 ± 11 beats per minute vs. 159 ± 12 beats per minute; Delta2 beats per minute; and ratings of perceived exertion 18 [14-20] units vs. 17 [14-20] units). In conclusion, supplementing with relatively high absolute doses of phosphate (i.e., >10 mmol daily for 4 days) exerted no ergogenic effects on trained cyclists completing 30-km time trials.